Management of Benign Prostatic Hyperplasia: Could Dietary Polyphenols Be an Alternative to Existing Therapies? - Eleazu, Chinedum; Eleazu, Kate; Kalu, Winner (Frontiers in Pharmacology, 2017)
The incidence of benign prostatic hyperplasia (BPH) is gradually on the increase. While conventional drugs such as the α1-adrenergic receptor antagonists and 5α-reductase inhibitors have been found to be useful in the treatment of BPH, the adverse side effects associated with their usage, have led to increased search for alternative means of managing this disease. Furthermore, although surgery has also been suggested to be a sure method, the cost and risks associated with it excludes it as a routine treatment. Dietary polyphenols have gained public interest in recent times due to their roles in the prevention of various diseases that implicate free radicals/reactive oxygen species. However, their roles in the management of BPH have not been explored. Hence this review on their prospects in the management of BPH and their mechanisms of action. Literature search was carried out in several electronic data bases such as Pubmed, Google Scholar, Medline, Agora and Hinari from1970 to 2017 to identify the current status of knowledge on this concept. The findings from these data bases suggest that while dietary polyphenols may not replace the need for the existing therapies in the management of BPH, they hold promise in BPH management which could be explored by researchers working in this field.